High quantum efficiency deep ultraviolet 4H‐SiC photodetectors. Issue 25 (1st December 2013) - Sampath, A.V.; Rodak, L.E.; Chen, Y.; Zhou, Q.; Campbell, J.C.; Shen, H.; Wraback, M.
Abstract : 4H‐SiC p ‐ n − ‐metal photodetectors are demonstrated having high external quantum efficiency >∼40% in the deep ultraviolet spectrum between 200 and 235 nm. This improvement is attributed to the improved collection of carriers generated by deep ultraviolet photons through absorption in the depletion region of the detector.